Research on Outdoor STEM Education in the Digital Age. Proceedings of the ROSETA Online Conference in June 2020 2020
DOI: 10.37626/ga9783959871440.0.03
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Everyday Mathematical Situations Outside the Classroom with MathCityMap and GeoGebra 3D

Abstract: In elementary school, teaching and learning activities aim to develop, among others, students skills to acquire deeper understanding of their living environments. There are numerous opportunities for students to recognize forms, shapes, and mathematical connections in everyday situations. These everyday situations can be simulated in classrooms; however, educational technologies offer new approaches to extend classroom activities, teachers can simulate and design shapes through Augmented Reality and 3D printin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…By combining visual, interactive and exploratory aspects, Geogebra-assisted discovery learning creates a learning environment that stimulates and supports holistic student development. Students not only understand mathematical concepts in the abstract, but they also see how these concepts apply in real-world contexts (Lavicza et al, 2020).…”
Section: Figure 1 Effect Size Of the Articlementioning
confidence: 99%
“…By combining visual, interactive and exploratory aspects, Geogebra-assisted discovery learning creates a learning environment that stimulates and supports holistic student development. Students not only understand mathematical concepts in the abstract, but they also see how these concepts apply in real-world contexts (Lavicza et al, 2020).…”
Section: Figure 1 Effect Size Of the Articlementioning
confidence: 99%
“…Although STEAM disciplines are still taught separately, the current curriculum in early childhood education in Luxembourg (MENJE, 2020b) requires teachers and educators to work in class with a transdisciplinary approach (Rausch et al, 2021) for STEAM disciplines (Liao, 2016), where arts are integrated in STEM (Lavicza et al, 2018). The integrated approach of STEAM disciplines (Kelley and Knowles, 2016;Haas et al, 2021b) has been shown to support students in applying discipline skills and understanding content more easily than taught separately (Burnard et al, 2018;Lavicza et al, 2020;El Bedewy et al, 2022). Moreover, this approach offers more creativity to the tasks and, thus, is likely to positively affect problem-solving skills of learning (Dana-Picard et al, 2021).…”
Section: Steam Transdisciplinary Approachmentioning
confidence: 99%
“…Although tutoring systems (Steenbergen-Hu and Cooper, 2013) prevailed in classes in primary education in past years, other technologies, which connected directly to the environment of students (e.g., CAD software, AR, or 3D printing), became more frequent in teaching. Thus, mixedrealities, such as the use of AR, where digital information is applied to the real-world information, were used to support students in visualizing mathematical concepts or explaining cultural or architectural phenomena (Ng, 2017;Liu et al, 2019;Lavicza et al, 2020). A representation of a shape in three dimensions in a real-world environment instead of a 2D representation gives the students a better understanding.…”
Section: Use Of Technology For 3d Modeling In Classmentioning
confidence: 99%
“…We carried out literature reviews on the use, in elementary school, on augmented reality (Bacca Acosta et al, 2019;Billinghurst & Duenser, 2012;Cai et al, 2019;González, 2015;Liu et al, 2019), as well as digital and physical mathematical modelling (Berdik, 2017;Haas et al, 2020;Lavicza et al, 2020;Lieban, 2019;Ng & Chan, 2019). Based on these literature reviews, we focused on four basic principles of Dienes's theory of mathematics (Dienes, 1960) to elaborate the tasks on mathematical modelling in remote teaching.…”
Section: Augmented Reality Digital and Physical Modellingmentioning
confidence: 99%
“…A long period where students would have learned and experimented with their teachers' topics in mathematics class, such as mathematical modelling with geometric shapes. Mathematical modelling is a central topic in mathematics education in elementary and it is learned through various hands-on learning activities (e.g., apply geometric shapes to real-world objects, combine objects to create shapes), which connect classroom learning to the student's everyday life Lavicza et al, 2020). Although, even in in-school settings, research showed that students encounter difficulties in mathematical modelling, while connecting real-life threedimensional worlds and two-dimensional space (González, 2015).…”
Section: Introductionmentioning
confidence: 99%